Inherited breast and ovarian cancer: a review of the available genetic counselling and testing services in Johannesburg - Jefferies, Marianne (My University, 2013)
Five to ten percent of both breast and ovarian cancer cases are attributable to dominantly inherited mutations in genes that predispose to cancer, with a large proportion caused by mutations in the breast and ovarian cancer predisposing genes BRCA1 and BRCA2. Testing for these inherited cancers is indicated for individuals identified as being at high risk, or moderate to high risk, of having a cancer syndrome based on their family history of breast and/or ovarian cancer. Screening for high-risk individuals through services such as genetic counselling, has the potential to improve outcomes for these individuals and lower mortality rates. This study focused on individuals who attended genetic counselling for breast and/or ovarian cancer at the Genetic Counselling Clinics of the Division of Human Genetics, University of the Witwatersrand and the National Health Laboratory Service, Johannesburg from 2001 to 2010. The study was divided into a file review on 218 counsellees and a telephonic interview of 50 counsellees. Focusing on breast and/or ovarian cancer, the study aimed to review who attends genetic counselling and why; who is offered genetic testing; what testing is offered and performed and; who pays for the testing, as well as gain a better understanding of how the service is received by counsellees. The study found that the majority of counsellees are white females, at a high risk of inherited breast and/or ovarian cancer, attend the genetic counselling session alone and are self-referred. There is an under representation of the black and coloured populations and an over representation of the Ashkenazi Jewish population in the cohort. The study‟s findings showed that a main motivator for individuals attending genetic counselling was for BRCA mutation testing, with the majority of testing offered being nationally based testing. The study also demonstrated that the service is generally well received and counsellees reported having a positive experience. Overall, the study pointed to the general lack of understanding and public awareness of genetic counselling, with suggestions to market to both the general population and to other medical professionals in order to reach more high risk individuals. On a practical level, a follow up service was suggested to ensure counsellees adhered to screening measures, informing counsellees on changes to testing protocols and identifying family members who may be at an increased risk of inherited breast and/or ovarian cancer.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Medicine in Genetic Counselling Johannesburg, 2013
Keywords: Ovarian Neoplasms; Breast Neoplasms; Health Services; Colorectal Neoplasms, Hereditary Nonpolyposis